Aesthetic management of anterior cantilever bridge with ovate pontic: a case report: Manajemen estetika jembatan kantilever anterior dengan pontik ovate: laporan kasus - Mariska Juanita; Irfan Dammar (Makassar Dental Journal PDGI Makassar, 2022)
This article describes a 16-year-old male who was referred to the Prosthodontics Department due to avulsion of the right upper central incisor and fracture of the left central incisor; the avulsed tooth was lost at the accident site. The patient refused to have his teeth prepared except for broken teeth so a single cantilever retainer denture bridge was made with fiber post design and ovate pontic. Radiographic examination was performed to evaluate the apical condition of the fractured tooth followed by initial im-pression for diagnostic wax-up, treated endodontically to prevent pulp necrosis. Preparation was carried out on tooth 21 using gingival retraction floss and the patient using provisory for 4 weeks. The final impression of the double impression technique was carried out with polyvinylsiloxane. The bridge is cemented using dual-cure resin cement. It is concluded that this ovate pontic design is very suitable for the treatment of the anterior region to achieve the best esthetic result as the main requirement.